Postmodern theories about readers in electronic environment (Libellarium: journal for research in the field of information and related sciences, 2015)
Introductory part of the paper discusses theories about readers in the last decades of the 20th century. In particular, two big theoretical schools are discussed: aesthetic reception theory and reader-response-criticism movement. Readers are a subject of very different scientific disciplines: literature theory, sociology, anthropology, book history and library science. The idea that a reader is an essential subject for future life of a literary work is common to all theorists. By constructing the theory about a reader, theorists have thought about the reader who uses the conventions of printed text. The issue whether these concepts correspond to electronic surroundings is discussed. Characteristics of the hypertext are emphasized as a new paradigm, and also the issue weather readers enjoys in hypertextual fiction. In conclusion, paper expands the virtual dimension of Isers's theory about interaction between the text and the reader, and also Fish's concept of “interpretative community” which may be constituted on the Internet as a flexible virtual community.
Keywords: postmodern theories about reader; reception theory; reader-response-criticism; hypertext; electronic text; author; reader